2013
DOI: 10.1177/0192623313477753
|View full text |Cite
|
Sign up to set email alerts
|

ACAT-selective and Nonselective DGAT1 Inhibition

Abstract: Acyl-coenzyme A: cholesterol O-Acyltransferase (ACAT) and Acyl-coenzyme A: diacylglycerol O-acyltransferase (DGAT) enzymes play important roles in synthesizing neutral lipids, and inhibitors of these enzymes have been investigated as potential treatments for diabetes and other metabolic diseases. Administration of a Acyl-coenzyme A: diacylglycerol O-acyltransferase 1 (DGAT1) inhibitor with very limited cellular selectivity over ACAT resulted in significant adrenocortical degenerative changes in dogs. These cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…We had previously shown that treating nanoparticle F at very high concentrations to mouse primary neurons in a culture did not produce obvious toxicities [ 48 ]. Previous work by others showed that when fed to mice for seven days, certain toxic ACAT inhibitors such as AZD3988 caused a significant reduction in fine vacuolation in cortical regions [ 55 ]. Here, we tested if nanoparticle F would produce toxicity in various tissues by giving IV injections of nanoparticle F to mice at 46 mg/kg once per day for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…We had previously shown that treating nanoparticle F at very high concentrations to mouse primary neurons in a culture did not produce obvious toxicities [ 48 ]. Previous work by others showed that when fed to mice for seven days, certain toxic ACAT inhibitors such as AZD3988 caused a significant reduction in fine vacuolation in cortical regions [ 55 ]. Here, we tested if nanoparticle F would produce toxicity in various tissues by giving IV injections of nanoparticle F to mice at 46 mg/kg once per day for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst this activity was only weak, the potential consequences of ACAT1 inhibition were believed to be severe enough to require a signicant margin between the two activities for a compound to be safe enough to progress. 6 This margin was set minimally at 100-fold, with an ideal compound having a margin signicantly in excess of this gure.…”
Section: Resultsmentioning
confidence: 99%
“…ACAT1 inhibitors were initially developed as potential cholesterollowering agents for cardiovascular disease. However, animal studies demonstrated marked adrenal toxicity from the drug, similar to mitotane, and establishing a potential role in adrenal tumors [64]. The role of ACAT inhibitors in ACC awaits further studies.…”
Section: Acat1mentioning
confidence: 99%